Sexually dimorphic therapeutic response in bortezomib-induced neuropathic pain reveals altered pain physiology in female rodents. Issue 1 (January 2020) - Stockstill, Katherine; Wahlman, Carrie; Braden, Kathryn; Chen, Zhoumou; Yosten, Gina L.; Tosh, Dilip K.; Jacobson, Kenneth A.; Doyle, Timothy M.; Samson, Willis K.; Salvemini, Daniela
Abstract : Abstract: Chemotherapy-induced neuropathic pain (CINP) in both sexes compromises many current chemotherapeutics and lacks an FDA-approved therapy. We recently identified the sphingosine-1-phosphate receptor subtype 1 (S1PR1) and A3 adenosine receptor subtype (A3 AR) as novel targets for therapeutic intervention. Our work in male rodents using paclitaxel, oxaliplatin, and bortezomib showed robust inhibition of CINP with either S1PR1 antagonists or A3 AR agonists. The S1PR1 functional antagonist FTY720 (Gilenya) is FDA-approved for treating multiple sclerosis, and selective A3 AR agonists are in advanced clinical trials for cancer and inflammatory disorders, underscoring the need for their expedited trials in patients with CINP as chemotherapy adjuncts. Our findings reveal that S1PR1 antagonists and A3 AR agonists mitigate paclitaxel and oxaliplatin CINP in female and male rodents, but failed to block or reverse bortezomib-induced neuropathic pain (BINP) in females. Although numerous mechanisms likely underlie these differences, we focused on receptor levels. We found that BINP in male rats, but not in female rats, was associated with increased expression of A3 AR in the spinal cord dorsal horn, whereas S1PR1 levels were similar in both sexes. Thus, alternative mechanisms beyond receptor expression may account for sex differences in response to S1PR1 antagonists. Morphine and duloxetine, both clinical analgesics, reversed BINP in female mice, demonstrating that the lack of response is specific to S1PR1 and A3 AR agents. Our findings suggest that A3 AR- and S1PR1-based therapies are not viable approaches in preventing and treating BINP in females and should inform future clinical trials of these drugs as adjuncts to chemotherapy. Abstract : We have found that there are sexually dimorphic responses to S1PR1 antagonists and A3 AR agonists for the treatment of bortezomib-induced neuropathic pain.